Tingkat Pendidikan Nelayan Di Pantai Utara Jawa Sebagai Faktor Mediasi Pengaruh Besaran Pendapatan Nelayan Terhadap Kesadaran Keselamatan Berlayar - Christine Widilestari; Amthori Anwar; Erwin Sutantyo (Jurnal Maritim Polimarin, 2019)
Awareness of sailing safety ls vital and must be prioritized. Various incidents of ship accidents, starting from burning ships and sinking became a separate evaluation material for Indonesia which declared it to be the world's maritime axis. The problem of the lack of safety equipment available on ships are found in cases of passenger ship accidents in Indonesia. This is also found in fishing vessels belonging to groups and individuals. The main reason stated by the ship owner is that the procurement of safety equipments requires no small amount of funds, and priority needs of each of the different safety equipments so that not all equipment need to be fulfilled, In addition, the low level of education and skills also affects safety awareness. The type of research used is Explanatory Research which aims to analyze whether or not the influence of the amount of fishermen's income on sailing safety awareness is mediated by education level. The number of research samples is 59 respondents who are fishermen on the North Coast of Java (Semarang, Demak, and Kendal). The research data was obtained through filling out questionnaires using a Likert scale with a range of 5. In addition, it was also strengthened by follow-up interviews to support the results of research data processing. From the results of the research data obtained results: (1) the amount of income did not affect the level of education, (2) the amount of income did not affect sailing safety awareness. (3) the level of education had a positive effect on sailing safety awareness and (4) the level of education was not mediates the effect of the amount of income on sailing safety awareness.